2015
DOI: 10.1159/000368702
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Pedunculopontine Nucleus Stimulation for Progressive Supranuclear Palsy

Abstract: The pedunculopontine nucleus (PPN) is a potential target for gait disorders. We report 4 cases of bilateral PPN stimulation in progressive supranuclear palsy (PSP) patients with short-term (6 months) and long-term (18 months) follow-ups. Patients with PSP who had gait disturbances, but were able to walk with or without assistance, were selected. The patients' median age was 64 years and the disease duration 3 years. Bilateral PPN deep brain stimulation (DBS) was performed. The pacemaker was programmed using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…To date, PPN DBS effects on PSP have been described in a few open studies with smaller samples of patients 3–6. One study with two patients with RS-PSP did not find clinical benefit in the UPDRS and PSPRS scores, although a minimal and transient gait improvement was observed 6. The other available studies involved different PSP phenotypes 3 4 6.…”
mentioning
confidence: 98%
“…To date, PPN DBS effects on PSP have been described in a few open studies with smaller samples of patients 3–6. One study with two patients with RS-PSP did not find clinical benefit in the UPDRS and PSPRS scores, although a minimal and transient gait improvement was observed 6. The other available studies involved different PSP phenotypes 3 4 6.…”
mentioning
confidence: 98%
“…Progressive supranuclear palsy might improve after PPN DBS [106], also combined with GPi [107]. Finally, ballism may respond to GPi DBS or Vop DBS [108].…”
Section: Other Movement Disordersmentioning
confidence: 99%
“…Much of the data concerning PPN DBS proposed for PD and a few PSP patients to alleviate FOG and falls has been extrapolated from experimental data . Although proof‐of‐concept clinical trials were promising, subsequent double‐blind trials reported heterogeneous and disappointing results . The difficulty of interpreting these results may be the result of factors, including clinical heterogeneity of patients and complexity of gait evaluation, with FOG being an intermittent symptom and difficult to pin point.…”
mentioning
confidence: 99%
“…24,25 Although proof-of-concept clinical trials were promising, subsequent double-blind trials reported heterogeneous and disappointing results. [26][27][28][29][30][31][32][33][34][35][36][37][38] The difficulty of interpreting these results may be the result of factors, including clinical heterogeneity of patients and complexity of gait evaluation, with FOG being an intermittent symptom and difficult to pin point. The major source of discrepancy remains the heterogeneity of the neurosurgical target between patients 37 and teams 36 because of the difficulty of delineating the PPN and CuN, which have indistinct boundaries.…”
mentioning
confidence: 99%